2019
DOI: 10.1002/jms.4470
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the interactions of the first 17 amino acid residues of Huntingtin with lipid vesicles using mass spectrometry and molecular dynamics

Abstract: The first 17 amino acid residues of Huntingtin protein (Nt17 of htt) are thought to play an important role in the protein's function; Nt17 is one of two membrane binding domains in htt. In this study the binding ability of Nt17 peptide with vesicles comprised of two subclasses of phospholipids is studied using electrospray ionization -mass spectrometry (ESI-MS) and molecular dynamics (MD) simulations. Overall, the peptide is shown to have a greater propensity to interact with vesicles of phosphatidylcholine (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 89 publications
(108 reference statements)
1
12
0
1
Order By: Relevance
“…More recently, a similar strategy was adopted to study lipid preferences of the N-terminal amphipathic helix of the huntingtin protein, aggregation of which is associated with amyotrophic lateral sclerosis. Valentine and co-workers used nMS to monitor the interactions of a peptide encompassing huntingtin residues 1-17 with lipid vesicles composed of different zwitterionic lipids [76]. By comparing the signal intensities and stoichiometries of the resulting complexes, the authors were able to show that peptide oligomerization is enhanced by the presence of vesicles, and preferential binding of doubly unsaturated lipids.…”
Section: Lipid Vesicles Preserve Specific Protein Interactions In Thementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a similar strategy was adopted to study lipid preferences of the N-terminal amphipathic helix of the huntingtin protein, aggregation of which is associated with amyotrophic lateral sclerosis. Valentine and co-workers used nMS to monitor the interactions of a peptide encompassing huntingtin residues 1-17 with lipid vesicles composed of different zwitterionic lipids [76]. By comparing the signal intensities and stoichiometries of the resulting complexes, the authors were able to show that peptide oligomerization is enhanced by the presence of vesicles, and preferential binding of doubly unsaturated lipids.…”
Section: Lipid Vesicles Preserve Specific Protein Interactions In Thementioning
confidence: 99%
“…• Based on these developments, we predict that nMS will enable new insights into elusive lipidprotein interactions. nMS has the potential to continue to make significant contributions to poorly understood disease mechanisms such as the membrane-mediated formation of protein aggregates in neurodegeneration [75], the mechanism of action of novel antimicrobial peptides [76], and lipid-encoded signaling in cancer [77]. • nMS can be integrated with other structural biology methods to yield detailed molecular models [81].…”
Section: Perspectivementioning
confidence: 99%
“…Eine erste Studie, die Liposomen mittels MS untersuchte, zeigte, dass Wechselwirkungen von bis zu 100 Lipidmolekülen in nativen MS‐Experimenten erhalten bleiben können [21] . Die Spezifität von Peptiden gegenüber bestimmten Lipiden wurde ebenfalls untersucht [21, 22] . In einer früheren Studie haben wir bereits verschiedene Phospholipide direkt aus den Lipiddoppelschichten von Liposomen identifiziert und quantifiziert [23] .…”
Section: Introductionunclassified
“…Recent structural investigations reveal high conformational plasticity of htt17 and the subsequent polyQ domain where htt17 association [26], its interactions with the membrane [43][44][45][46][47] or with other polypeptide domains are associated with random coil-helix structural transitions [48,49]. A recent NMR study has shown that in the solution, the htt17 sequence associates in a dimer of dimers preaggregation state [50,51].…”
Section: Introductionmentioning
confidence: 99%